The Role of Liquid Biopsy in Early Diagnosis of Lung Cancer - Freitas, Cláudia; Sousa, Catarina; Machado, Francisco; Serino, Mariana; Santos, Vanessa; Cruz-Martins, Natália; Teixeira, Armando; Cunha, António; Pereira, Tania; Oliveira, Hélder P.; Costa, José Luís; Hespanhol, Venceslau (Frontiers in Oncology, 2021)
Liquid biopsy is an emerging technology with a potential role in the screening and early detection of lung cancer. Several liquid biopsy-derived biomarkers have been identified and are currently under ongoing investigation. In this article, we review the available data on the use of circulating biomarkers for the early detection of lung cancer, focusing on the circulating tumor cells, circulating cell-free DNA, circulating micro-RNAs, tumor-derived exosomes, and tumor-educated platelets, providing an overview of future potential applicability in the clinical practice. While several biomarkers have shown exciting results, diagnostic performance and clinical applicability is still limited. The combination of different biomarkers, as well as their combination with other diagnostic tools show great promise, although further research is still required to define and validate the role of liquid biopsies in clinical practice.